What Is Logic? - Rumfitt, Ian (Truth, Reference and Realism, 2011)
What is logic? Textbooks typically introduce the subject as the science of consequence. Thus in an early section of his estimable primer-a section entitled "What Logic Is About"-we find Benson Mates explaining that logic investigates the relation of consequence that holds between the premises and the conclusion of a sound argument. An argument is said to be sound (correct, valid) if its conclusion follows from or is a consequence of its premises; otherwise it is unsound.1 (Mates 1965, 2)